Optimizing the Performance of the Patrol Unit of the Samapta Unit, Sorong City Police, in Preventing Motor Vehicle Theft (Curanmor) to Realize a Conducive Public Security and Order (Harkamtibmas) - Meiland Makalisang; Victor P. K. Lengkong; Rita N. Taroreh; Christoffel M. O. Mintarjo (Journal of Comprehensive Science, 2026)
Motor vehicle theft (curanmor) is one of the most disturbing crimes and dominates conventional crime rates in various regions of Indonesia, including Sorong City. As the frontline in maintaining public security and order, the Samapta Unit of the Sorong City Police has a strategic role through preventive patrol activities to prevent motor vehicle theft. This research aims to analyze the effectiveness of the Patrol Unit of Satuan Samapta Polresta Sorong City in preventing motor vehicle theft (curanmor) in order to achieve a conducive state of public security and order (Harkamtibmas). A qualitative approach was applied using observation, semi-structured interviews, and documentation. The research focuses on patrol strategies, personnel workload, fleet utilization, and community collaboration, especially with motorcycle taxi communities. The findings indicate that preventive patrols play a crucial role in reducing curanmor incidents, although personnel capacity and infrastructure remain limited. Strategies such as the "Blue Light Patrol," quick response units, and community partnerships have proven effective in early detection and crime prevention. Nevertheless, geographic challenges, population density, and motor vehicle growth require ongoing innovation and optimization. The study recommends enhancing inter-agency coordination, improving human resource capacity, and upgrading facilities to maximize patrol effectiveness in ensuring public safety.